2009
DOI: 10.1002/mc.20555
|View full text |Cite
|
Sign up to set email alerts
|

Using cells devoid of RAS proteins as tools for drug discovery

Abstract: Mutational activation of RAS proteins occurs in nearly 30% of all human tumors. To date direct pharmacological inhibition of RAS oncoproteins has not been possible. As a consequence, current strategies are focusing on the development of inhibitors that target those kinases acting downstream of RAS proteins, including those of the RAF/MEK/ERK and PI3K/AKT pathways. Most of these inhibitors have undesired off-target effects that mask the potential therapeutic effect of blocking their targeted kinases. To facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…To further examine the potential RAS-dependent lethality of 3144, we used a previously reported mouse embryo fibroblast (MEF) cell line in which murine Hras and Nras had been deleted, and only Kras remained, flanked by loxP sites; a tamoxifen-inducible Cre recombinase was also expressed in these Kras lox/lox , Hras −/− , Nras −/− RERTn ert/ert cells (Urosevic et al, 2009). We found that these cells were sensitive to the lethality of compound 3144, as expected (IC 50 = 3.8 μM, Figure 3B); however, excision of Kras from these cells using tamoxifen, and introduction of membrane-targeted BRAF V600E -CAAX resulted in resistance to 3144 (Figure 3B), indicating a degree of Kras -dependent lethality.…”
Section: Resultsmentioning
confidence: 99%
“…To further examine the potential RAS-dependent lethality of 3144, we used a previously reported mouse embryo fibroblast (MEF) cell line in which murine Hras and Nras had been deleted, and only Kras remained, flanked by loxP sites; a tamoxifen-inducible Cre recombinase was also expressed in these Kras lox/lox , Hras −/− , Nras −/− RERTn ert/ert cells (Urosevic et al, 2009). We found that these cells were sensitive to the lethality of compound 3144, as expected (IC 50 = 3.8 μM, Figure 3B); however, excision of Kras from these cells using tamoxifen, and introduction of membrane-targeted BRAF V600E -CAAX resulted in resistance to 3144 (Figure 3B), indicating a degree of Kras -dependent lethality.…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis we employed an experimental system that allowed us to study signal transduction by ectopic N-Ras variants in the absence of confounding signals by endogenous Ras proteins. H-Ras − / − , N-Ras − / − , K-Ras lox/lox , RERT ert/ert MEFs (from here on K-Ras lox/lox ), a mouse embryonic cell line engineered and characterized by Barbacid and co-workers [38,39], carries knockout H-Ras and N-Ras alleles, floxed K-Ras loci and inducible Cre recombinase. Recombinase induction with 4-OHT leads to excision of the K-Ras alleles, rendering the K-Ras lox/lox MEFs devoid of all three Ras proteins.…”
Section: Palmitoylation-deficient N-ras Does Not Transmit Mitogenic Smentioning
confidence: 99%
“…As Erk is directly activated by the mitogen-activated protein kinase (MAPK) kinase (MEK), we used the specific MEK inhibitor U0126 (Favata et al, 1998;Urosevic et al, 2009) to prevent Erk activation in the in vitro B cell differentiation assay. As shown in Fig.…”
Section: Low Bcr Expression Inhibits the Differentiation Of Immature mentioning
confidence: 99%